The P0 protein encoded by cotton leafroll dwarf virus (CLRDV) inhibits local but not systemic RNA silencing - Delfosse, Veronica Cecilia; Agrofoglio, Yamila Carla; Casse, Maria Florencia; Bonacic Kresic, Iván; Hopp, Horacio Esteban; Ziegler-Graff, Véronique; Distefano, Ana Julia (2018)
Plants employ RNA silencing as a natural defense mechanism against viruses. As a counter-defense, viruses encode silencing suppressor proteins (SSPs) that suppress RNA silencing. Most, but not all, the P0 proteins encoded by poleroviruses have been identified as SSP. In this study, we demonstrated that cotton leafroll dwarf virus (CLRDV, genus Polerovirus) P0 protein suppressed local silencing that was induced by sense or inverted repeat transgenes in Agrobacterium co-infiltration assay in Nicotiana benthamiana plants. A CLRDV full-length infectious cDNA clone that is able to infect N. benthamiana through Agrobacterium-mediated inoculation also inhibited local silencing in co-infiltration assays, suggesting that the P0 protein exhibits similar RNA silencing suppression activity when expressed from the full-length viral genome. On the other hand, the P0 protein did not efficiently inhibit the spread of systemic silencing signals. Moreover, Northern blotting indicated that the P0 protein inhibits the generation of secondary but not primary small interfering RNAs. The study of CLRDV P0 suppression activity may contribute to understanding the molecular mechanisms involved in the induction of cotton blue disease by CLRDV infection.